Contesto storico e avanguardie europee: il caso del futurismo italiano - RUFINO , Ugo (Cuadernos de Filología Italiana, 2010)
The figure and the work of the volcanic Marinetti express the image of an European intellectual: his artistic-literary theory exalts the break with the past and defend the technological age, which is one of the basis of the first vanguard Italian movement, at the beginning of the XX century. Its contents cross the national boundaries, invading European metropolis with exhibitions, lectures, theatre representations and polemical manifestos, which will be very succesful. The futuristic themes, which were common to other vanguard movements, will give life to new cultural products, in relation to the needs of the rising mass society, and they will receive a wide international reception in the intellectual european circles. In Italy the Futurism will contribute to the renewal of the national culture, crossing and conditioning, by its polemic and trasgressive verve the beginning of the century through a poetical language radically innovative, based on parole in libertà and immaginazione senza fili.